Effect of Atorvastatin in Lipid Profile Changes and Inflammation Marker TNF-alpha on Diabetes Patient with Dyslipidemia - Melasari, Wulan Panduwi; Suharjono, Suharjono; Samsulhadi, Wiwid (Folia Medica Indonesiana, 2021)
Diabetes is one of the risk factors for cardiovascular disease (CVD). Diabetics patients have 2 to 4 times increased risk of cardiovascular disease compared with non-diabetics. TNF-alpha is a proinflammatory cytokine that can be used to determine the risk of atherosclerosis complications triggered by inflammation in diabetes. Statins are a class of HMG CoA reductase inhibitors that inhibit cholesterol biosynthesis and have pleioropic effects that inhibit the release of inflammatory cytokines like TNF-alpha and stabilize atherosclerotic plaques. This study aims to determine the effect of atorvastatin 20 mg/day for 30 days in reducing the lipid profile and TNF-alpha inflammatory markers in patients with diabetes dyslipidemia. Diabetes patient with dyslipidemia who included the inclusion criteria in this observational prospective cohorts studies treated with atorvastatin for 30 days (n = 19). The efficacy of statin therapy was measured by lipid profiles (LDL, TG, HDL, and total cholesterol) and TNF-alpha. The results of the study showed that atorvastatin decreased 40.55% of LDL levels, 15.34% of TG levels, and 30.70% oftotal cholesterol levels which statistically significant (P <0.05). As for HDL, there is an increase of 6.06% but statistically non-significant (P >0.05). TNF-alpha levels increased by 11.30% which statistically non-significant (P >0.05). The use of atorvastatin 20 mg for 30 days gave reduction in LDL, TG, and total cholesterol and increased in HDL. Atorvastatin does not have a reducing effect on TNF-alpha. There was no correlation between lipid profile changes with TNF-alpha changes.